Activism of pension funds and corporate governance quality - Punsuvo, Fábio Riberi; Kayo, Eduardo Kazuo; Barros, Lucas Ayres Barreira de Campos (Revista Contabilidade & Finanças, 2007)
Pension funds are institutional investors of great relevance to capital markets in Brazil and abroad. As their ownership of public companies grows, pension funds tend to intensify their monitoring on the managers of incumbent companies. Using their prerogative as important shareholders, pension funds are able to exercise these monitoring activities more actively. Thus, the main objetive of this article is to analyze the relationship between the pension fund's ownership and the quality of corporate governance of the incumbent companies. Results show a negative relation between these variables, suggesting a possible tradeoff between ownership and corporate governance as mechanisms of alignment between pension funds and companies.